Prioritization of Referrals in Outpatient Physiotherapy Departments in Québec and Implications for Equity in Access - Deslauriers, Simon; Raymond, Marie-Hélène; Laliberté, Maude; Hudon, Anne; Desmeules, François; Feldman, Debbie E.; Perreault, Kadija (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
In the context of long waiting time to access rehabilitation services, a large majority of settings use referral prioritization to help manage waiting lists. Prioritization practices vary greatly between settings and there is little consensus on how best to prioritize referrals. This paper describes the prioritization processes for physiotherapy services in Québec and its potential implications in terms of equity in access to services. This is a secondary analysis of a survey of outpatient physiotherapy departments (n=98; proportion of participation was 99%) conducted in 2015 across publicly funded hospitals in Québec. In many settings, persons with acute orthopaedic conditions were prioritized while chronic conditions were given a lower priority. There were 72 different combinations of prioritization criteria used in outpatient physiotherapy departments. Variability was also observed in the type of personnel involved in the prioritization process, the number of priority levels used to rank the referrals and the source of information used to prioritize referrals. These results highlight potential issues regarding equity in access to physiotherapy services: the prioritization of persons with acute conditions to the detriment of those with chronic conditions, the lack of consensus on a fair prioritization process and the importance to adequately assess patients’ needs for treatment. Further research and interventions on prioritization criteria and processes are needed to ensure equitable access to physiotherapy services, especially in the public sector.